ANALISIS KERUSAKAN LINGKUNGAN AKIBAT PERTAMBANGAN PASIR DI SUNGAI PROGO - Eko Teguh Paripurno; Awang Hendrianto Pratomo; Purbudi Wahyuni; Nandra Eko Nugroho; Wahyu Sugeng Triadi; Gigih Aditya Pratama; Sukiyani; Wana Kristanto; Gandar Mahojwala (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
ANALYSIS OF ENVIRONMENTAL DAMAGE DUE TO SAND MINING IN THE PROGO RIVER Mining activities can significantly impact the physical environment, particularly in areas close to critical infrastructures such as rivers and residential buildings. This research purposively choose a corporation mining activities in the Progo River to being evaluated in the context of envionmental damage. This study aims to assess the extent of environmental damage in and around of corporation mining concession area, specifically focusing on river degradation, erosion, and structural instability. The goal is to classify the damage according to established environmental criteria and determine the severity of the impact. The research utilized aerial photographs, satellite imagery, and photos obtained from drones. These were first processed using photogrammetry software, followed by geometric correction on the images to eliminate perspective distortion and topographic tilt, resulting in an accurate orthophoto. The orthophoto was then analyzed spatially using a Geographic Information System (GIS).. The assessment was carried out using the criteria and benchmarks provided by the Governor's Decree of the Special Region of Yogyakarta No. 63 of 2003. The findings indicate significant environmental damage due to PT A’s mining activities. River flow changes were identified, with a shift to a meandering pattern and the formation of deep troughs in the riverbed. Based on the analysis, the environmental damage caused by PT A’s mining activities falls into the category of severe damage. The degradation of the river, erosion of land, and instability of nearby infrastructure necessitate urgent attention and mitigation efforts to prevent further environmental harm.